Section 230(c)(1) of the Communications Decency Act and the Common Law of Defamation: A Convergence Thesis - Sharp-Wasserman, Julio (Science and Technology Law Review, 2019)
Section 230 of the Communications Decency Act (CDA), codified in the early days of the Internet, immunizes online intermediaries, such as operators of websites, from liability for the speech or conduct of their users. The impact of this provision has been not only profound, but also controversial, partly because it has been applied with rigid consistency in a wide variety of legal contexts, from defamation to housing discrimination to false advertising to human trafficking. This Note proposes that the judicial application of CDA § 230 to defamation liability is unique, in that defamation law would not be measurably different if Congress had not passed this provision. This thesis has a doctrinal component: courts applying the common law of defamation, which incorporates First Amendment law, likely would reach similar conclusions to courts applying CDA § 230 to defamation liability. This thesis also incorporates a comparison of legal realities in defamation cases against online intermediaries. First, there likely would be a comparable degree of legal uniformity in defamation law across jurisdictions. Second, and especially relevant from the standpoint of litigation costs, pre-trial dismissal would be available under the same circumstances. The implications of this thesis are debatable: this Note might undermine the wisdom of other applications of CDA § 230 that do not implicate freedom of speech concerns; however, it certainly bolsters the constitutional legitimacy of CDA § 230’s application to speech torts.